1995
DOI: 10.2165/00002512-199507050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Intervention in Older Patients with Rheumatoid Arthritis

Abstract: Despite the rather pessimistic outlook regarding the long term effects of pharmacological treatment of patients with rheumatoid arthritis (RA), there is no doubt that drug interventions can affect quality of life (QOL). The disease has a significant impact upon physical, psychological and social function, and QOL optimisation should cover all these dimensions. Swelling of joints and pain are important manifestations in assessing RA since these may result in sleep disturbances as well as depressed mood. This mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…There has been a report 24 that showed a transient quality of life improvement in older RA patients due to the use of drugs, and the results of the present study also showed that the use of drugs can improve emotional instability. There has been a report 24 that showed a transient quality of life improvement in older RA patients due to the use of drugs, and the results of the present study also showed that the use of drugs can improve emotional instability.…”
Section: Medication (Drug Use)supporting
confidence: 74%
“…There has been a report 24 that showed a transient quality of life improvement in older RA patients due to the use of drugs, and the results of the present study also showed that the use of drugs can improve emotional instability. There has been a report 24 that showed a transient quality of life improvement in older RA patients due to the use of drugs, and the results of the present study also showed that the use of drugs can improve emotional instability.…”
Section: Medication (Drug Use)supporting
confidence: 74%
“…27 Besides this, early detection and intervention of medication errors or adverse drug reactions may save follow-up costs and improve patients’ quality of life. 2830…”
Section: Discussionmentioning
confidence: 99%
“…This will forcibly have a high impact on the results of treatment in clinical practice. Expectations regarding the effects and side effects of therapy are essential for successful adherence [135]. Female gender, middle age, busy lifestyle, cognitive deficits, depression, higher income, and employment status have all been associated with nonadherence [136,137].…”
Section: Adherence Beliefs Expectations and Communicationmentioning
confidence: 99%
“…Psychological aspects of the prescribing physician and divergence between patients and physicians also play a role. For example, patients with early RA were less reluctant to accept combination therapy with conventional DMARDs and biologics than rheumatologists [133][134][135][136], and a study analyzing the European League Against Rheumatism Recommendations on the management of glucocorticoid therapy demonstrated important discrepancies between patients' and rheumatologists' perspectives that might negatively affect the implementation of the recommendations [137]. Such beliefs and divergence need to be addressed, as they may unduly interfere with the physician's selection of therapy and with the patient's commitment to the strategy.…”
Section: Adherence Beliefs Expectations and Communicationmentioning
confidence: 99%